Uncovering Fraud in Health Center Capitation Fund Planning - Akbar, Muhammad; Prasetyono, Prasetyono; Tarjo, Tarjo (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 1 (2024), 2024)
The purpose of this study was to uncover fraud in the management of capitation funds at the Pesisir Health Center in Sanjaya Regency. This research was conducted to determine the copy in the capitation fund management plan. This study uses a qualitative method with a case study approach methods of data collection in this study by way of observation, documentation, and interviews. The results of the study show that there are several findings, among others. First, the perpetrators of capitation fund fraud are due to pressure factors, one of which is financial, in getting more benefits from capitation funds, so that this pressure encourages the perpetrators to commit capitation fund fraud. Second, there are opportunities where fraud is carried out by perpetrators because there are opportunities in monitoring the management of capitation funds so that fraud perpetrators can easily commit fraud. Third, there is a rationalization in which the perpetrators consider capitation fund fraud to be a natural thing because in recent years many other actors have done it to benefit from capitation funds, so they think that profiting from capitation funds is a natural thing. Fourth, there is the ability where the fraud committed by the perpetrators on average has the abilities and habits of the perpetrators, so that without difficulty they commit capitation fund fraud.